2019
DOI: 10.1017/s175173111900034x
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: β-hydroxybutyrate concentration in blood and milk and its associations with cow performance

Abstract: Hyperketonemia (HYK) is one of the most frequent and costly metabolic disorders in high-producing dairy cows and its diagnosis is based on β-hydroxybutyrate (BHB) concentration in blood. In the last 10 years, the number of papers that have dealt with the impact of elevated BHB levels in dairy cattle has increased. Therefore, this paper reviewed the recent literature on BHB concentration in blood and milk, and its relationships with dairy cow health and performance, and farm profitability. Most studies applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 49 publications
8
85
1
5
Order By: Relevance
“…Likewise, the feasibility of using spectral data to predict glucose, NEFA, BUN, and IGF-1 were also investigated in this review ( Table 10). The R 2 reported by the authors varied between 0.20 (glucose; Benedet et al, 2019) to 0.61 (IGF-1; Grelet et al, 2019) in the validation set.…”
Section: Health Statusmentioning
confidence: 94%
See 1 more Smart Citation
“…Likewise, the feasibility of using spectral data to predict glucose, NEFA, BUN, and IGF-1 were also investigated in this review ( Table 10). The R 2 reported by the authors varied between 0.20 (glucose; Benedet et al, 2019) to 0.61 (IGF-1; Grelet et al, 2019) in the validation set.…”
Section: Health Statusmentioning
confidence: 94%
“…Subclinical hyperketonemia or ketosis is one of the most frequent diseases in dairy cattle and it is characterized by increased concentrations of the ketone bodies acetoacetate, β-hydroxybutyrate (BHB), and acetone in blood, milk, and urine (Hansen, 1999). Additionally, blood metabolites such as glucose, non-esterified fatty acids (NEFA), blood urea nitrogen (BUN), and insulin-like growth factor 1 (IGF-1), and glutamic oxaloacetic transaminase (GOT) might also be used as indicators of metabolic status in dairy cows (Fenwick et al, 2008;Benedet et al, 2019;Grelet et al, 2019). Blood metabolic profile testing is the gold standard for diagnosis, however, it is invasive, logistically challenging, and costly (Luke et al, 2019).…”
Section: Health Statusmentioning
confidence: 99%
“…different methods of data collection, different calculation techniques and lengths of interval at risk. For example Kelton et al (1998) suggested two approaches for retrospective and current analysis, and Østerås et al (2007) defined the base population as the number of cow-years, while Pryce et al (2016) or Benedet et al (2019) pointed out the difference between the prevalence and incidence of disease, as these terms are not always used correctly, which made the interpretation of results difficult. Generally, Kelton et al (1998) stated in their older meta-analysis that the LIR ranged between 0.03 - 22.3% with median 6.5% for PAR, 1.3 -39.2% with median 8.6% for REP, 2.2 - 37.3% with median 10.1% for MET (different definition of the trait), 1.3 - 18.3% with median 4.8% for KET, 0.3 -6.3% with median 1.7% for left DA, and finally 1.0 -16.1% with median 8.0% for CYS.…”
Section: Discussionmentioning
confidence: 99%
“…For metabolic disorders, where under-reporting could be a challenge, a suitable predictor is often being suggested, which would be especially valuable, if it could be measured objectively (Pryce et al, 2016). Different studies have already been aimed at fat-to-protein ratio, β-hydroxybutyrate concentration in milk, or body condition score (Jamrozik et al, 2016;Benedet et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This trend was previously reported by Mäntysaari et al [25] for Nordic Red cows. The increase of blood BHB and NEFA concentrations with parity is generally expected [26,27]. However, elevated concentrations of BHB and NEFA in the blood of first-lactation cows could be due to their concurrent energy demands for growth and lactogenesis or a worse energy status than multiparous cows around calving [28,29].…”
Section: Interaction Effectsmentioning
confidence: 99%